2018
DOI: 10.2519/jospt.2018.7866
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric Testing of the Lumbar Spine Instability Questionnaire

Abstract: Study Design Clinical measurement study. Background The Lumbar Spine Instability Questionnaire (LSIQ) is a self-report measure of 15 items. Previous studies have used the LSIQ as a measure of clinical instability; however, a comprehensive evaluation of its clinimetric properties has not been conducted. Objectives The aim of this study was to evaluate the clinimetric properties of the LSIQ in patients with chronic non-specific low back pain (LBP). Methods We included patients with non-specific LBP presenting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“… 12 Subsequently, the questionnaire was translated into Thai and Brazilian Portuguese 13 , 14 and its reliability tested. 13 – 15 Chatprem et al 13 (in press) developed a Thai version of the lumbar instability screening tool for physical therapists to administer to patients with CLBP.…”
mentioning
confidence: 99%
“… 12 Subsequently, the questionnaire was translated into Thai and Brazilian Portuguese 13 , 14 and its reliability tested. 13 – 15 Chatprem et al 13 (in press) developed a Thai version of the lumbar instability screening tool for physical therapists to administer to patients with CLBP.…”
mentioning
confidence: 99%
“…A recent summary of the CPGs recommends exercise as an intervention for primary management of patients with chronic LBP and for use in selected patients with acute LBP . Numerous forms of exercise are available for management of LBP, ranging from general physical activity (eg, walking) to core‐specific exercises (eg, motor control) . A Cochrane review reported that motor control exercises are not superior to other forms of exercise .…”
Section: Treatment Approaches For Joint Stabilizationmentioning
confidence: 99%
“…35 The Lumbar Spine Instability Questionnaire is a 15-item questionnaire that may be useful in assessing instability and guiding treatment approaches. 36,37 A thorough kinematic evaluation of bilateral lumbopelvic movement symmetry can provide important information for the management of patients with LBP. 15…”
Section: Kinematics Gait Motor Control and Muscular Functionmentioning
confidence: 99%
See 2 more Smart Citations